Visual perception from a computer graphics perspective - Thompson, William B. , 1948- (CRC Press, 2011)
"This book introduces human visual perception to readers studying or working in the field of computer graphics, though it may also be of use to perceptual psychologists using computer graphics to generate experimental stimuli, directly investigating the perceptual effectiveness of some aspect of computer graphics, or interested in perceptual topics relevant to the information content of images but not included in most standard vision science references. The book can be used either as a text for an advanced undergraduate or graduate course or as an overview of perception for those active as researchers or developers in computer graphics or related fields"